2012
DOI: 10.1186/1471-2180-12-278
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a ferritin-like protein of Listeria monocytogenes as a mediator of β-lactam tolerance and innate resistance to cephalosporins

Abstract: BackgroundThe food-borne pathogen Listeria monocytogenes is the causative agent of listeriosis. The β-lactam antibiotics penicillin G and ampicillin are the current drugs of choice for the treatment of listerial infections. While isolates of L. monocytogenes are susceptible to these antibiotics, their action is only bacteriostatic and consequently, this bacterium is regarded as tolerant to β-lactams. In addition, L. monocytogenes has a high level of innate resistance to the cephalosporin family of β-lactams fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…It has recently been shown that the Fri protein of L. monocytogenes plays a crucial role in cell death caused by β-lactam antibiotics [20]. Detailed studies were undertaken to define the involvement of Fri in the maintenance of L. monocytogenes cell envelope structure and stability under β-lactam pressure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has recently been shown that the Fri protein of L. monocytogenes plays a crucial role in cell death caused by β-lactam antibiotics [20]. Detailed studies were undertaken to define the involvement of Fri in the maintenance of L. monocytogenes cell envelope structure and stability under β-lactam pressure.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we compared the properties of wild-type strain EGD and the Δ fri mutant grown in both the absence and presence of 0.09 µg/ml of penicillin G (corresponds to 0.75 of the MIC value). These β-lactam stress conditions were previously shown to permit efficient growth of both strains, but caused slight growth retardation of strain Δ fri compared to the wild type [20]. To examine the role of Fri in maintaining the integrity of the L. monocytogenes cell envelope under β-lactam pressure, the susceptibility of the studied strains to lysis induced by incubation with the cell wall hydrolase lysozyme was assessed (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations